2011
DOI: 10.1172/jci57984
|View full text |Cite
|
Sign up to set email alerts
|

Foxo1 is required in mouse spermatogonial stem cells for their maintenance and the initiation of spermatogenesis

Abstract: Spermatogonial stem cells (SSCs) capable of self-renewal and differentiation are the foundation for spermatogenesis. Although several factors important for these processes have been identified, the fundamental mechanisms regulating SSC self-renewal and differentiation remain unknown. Here, we investigated a role for the Foxo transcription factors in mouse spermatogenesis and found that Foxo1 specifically marks mouse gonocytes and a subset of spermatogonia with stem cell potential. Genetic analyses showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
251
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(267 citation statements)
references
References 53 publications
15
251
1
Order By: Relevance
“…Moreover, the absence of a new wave of spermatogenesis showed that self-renewal of SSCs is impaired in the absence of PELO. The dramatic disruption of spermatogenesis in Pelo-deficient mice is similar to that observed in mice lacking the Plzf, Etv5, Foxo1, or Shp2 genes, which regulate the self-renewal of SSCs (Costoya et al 2004, Simon et al 2007, Goertz et al 2011, Puri et al 2014.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Moreover, the absence of a new wave of spermatogenesis showed that self-renewal of SSCs is impaired in the absence of PELO. The dramatic disruption of spermatogenesis in Pelo-deficient mice is similar to that observed in mice lacking the Plzf, Etv5, Foxo1, or Shp2 genes, which regulate the self-renewal of SSCs (Costoya et al 2004, Simon et al 2007, Goertz et al 2011, Puri et al 2014.…”
Section: Discussionmentioning
confidence: 52%
“…6A, the levels of nuclear FOXO1 were significantly reduced in mutants compared with controls. We then investigated the expression levels of Lhx1, Ret, Sall4, and Dppa3 by qRT-PCR, whose expression levels were significantly attenuated in the testes of Foxo1-null mice (Goertz et al 2011). The expression levels of Sall4 and Dppa3 were significantly lower in mutant P7 and P14 testes compared with controls, whereas no significant differences were detected in the expression levels of Lhx1 and Ret between control and mutant testes (Fig.…”
Section: Attenuation Of Transcriptional Activity Of Foxo1 Impairs Thementioning
confidence: 99%
See 2 more Smart Citations
“…Self-renewal and differentiation of rodent SSCs including mouse (5), rat (6,7), and hamster (8), depend on the response to the growth factor glial cell line-derived neurotrophic factor (GDNF). By binding to the glycosylphosphatidylinositol-anchored cell surface molecule of GDNF family receptor alpha1 (GFRα1), GDNF is able to trigger the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) pathway and up-regulate expression of POU3F1 and eventually lead to survival and proliferation of SSCs (9)(10)(11) (Figure 1). …”
Section: Introductionmentioning
confidence: 99%